P.036 Stroke in people with Down Syndrome: a retrospective study. (June 2019) - Cieuta-Walti, C; Mircher, C; Marey, I; Toulas, J; Walti, H; Conte, M; Rebillat, A; Ravel, A
Abstract : Background: There are only few studies approaching the prevalence and cause of stroke in children and adults with Down Syndrome (DS). Methods: We did a retrospective study of our cohort of 4962 patients of Jerome Lejeune Institute since 2007. We collected age of stroke, clinical presentation, cause (TOAST classification), treatment and clinical course. Results: We identified 20 patients from 6 to 56 years old .In all cases, it was a stroke of ischemic origin.: 8 children with a prevalence of 0.33%. 4 had a cardio-embolic origin, 3 secondary to Moya-Moya syndrome and one of undetermined origin. 12 adults (21 to 52 years old) with a prevalence of 0.46%.The majority of the causes of these ischemic strokes are indeterminate (9 of 12), Conclusions: We found a low prevalence and an ischemic cause in all cases of stroke, which differs from the general population. For pediatric stroke, the causes are expected thromboembolic in a context of heart disease most often or secondary to a Moya-Moya syndrome. For adult strokes, the average age is younger than that in the general population and the cause is indeterminate in most cases. We must better explore our patients to identify the risk factors in DS population.